In situ generation of hydrogen peroxide from reaction of O-2 with hydroxylamine from hydroxylammonium salt in neutral aqueous or non-aqueous medium using reusable Pd/Al2O3 catalyst - Choudhary, Vasant R.; Jana, Prabhas (Catalysis Communications, 2007)
In situ generation of H2O2 with high yield can be accomplished by reacting 02 with NH2OH from hydroxylammonium salt [NH2OH.HCl or (NH2OH)(2) . H2SO4] in a neutral aqueous medium using a reusable heterogeneous Pd (1.0 wt%)/Al2O3 catalyst, even at low temperature (10 degrees C), with the formation of harmless by-products (viz. N-2 and water). The presence of KCl or KBr in the medium has beneficial effect. The H2O2 generation is strongly influenced by the pH of medium, reaction period and temperature; best results are obtained at the optimum pH and reaction medium. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Hydrogen peroxide; hydroxylamine; Hydroxylammonium salt; in situ H2O2 generation; oxygen; Pd/AlO3 catalyst